Thermal treatment of sewage sludge in Germany: A review. (1st June 2020) - Schnell, Matthias; Horst, Thomas; Quicker, Peter
Abstract: Sewage sludge from municipal wastewater treatment plants in Germany is currently disposed of via thermal treatment and agricultural utilization or used for landscaping. Increasing focus on hygiene, soil protection and most recently on phosphorus recovery combined with the associated legal changes leads to an increased relevance of thermal sewage sludge treatment processes. This article reviews existing technologies for thermal treatment of sewage sludge with a view to the situation in Germany. Thermal sewage sludge treatment can be divided into different processes: drying reduces high water contents of mechanically dewatered sewage sludge and often precedes subsequent treatment processes. Today, most of the sewage sludge in Germany is incinerated, about half in mono-incineration, mostly in stationary fluidized beds, and the other half in co-incineration, in particular in coal-fired power plants, cement kilns or, to a lesser extent, waste incineration plants. Some alternative thermal processes, mainly pyrolysis and gasification, but also metallurgical approaches, are tested in bench or pilot scale. Recent amendments to the German Sewage Sludge Ordinance will restrict the disposal route of co-incineration in future. Consequently, a significant increase in mono-incineration capacity is expected. These processes should enable the combination of environmentally friendly disposal and phosphorus recovery. Highlights: Previous treatment paths for sewage sludge are compared with the current status. Recently amended legal framework for sewage sludge treatment is summarized. Current and past most common processes for mono-incineration are reviewed. Disadvantages of co-incineration and alternative technologies are presented. Future development of sewage sludge treatment is assessed on basis of this research.